2016
DOI: 10.1172/jci.insight.88942
|View full text |Cite
|
Sign up to set email alerts
|

Vascular mineralocorticoid receptor regulates microRNA-155 to promote vasoconstriction and rising blood pressure with aging

Abstract: Hypertension is nearly universal yet poorly controlled in the elderly despite proven benefits of intensive treatment. Mice lacking mineralocorticoid receptors in smooth muscle cells (SMC-MR-KO) are protected from rising blood pressure (BP) with aging, despite normal renal function. Vasoconstriction is attenuated in aged SMC-MR-KO mice, thus they were used to explore vascular mechanisms that may contribute to hypertension with aging. MicroRNA (miR) profiling identified miR-155 as the most down-regulated miR wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 67 publications
4
88
0
4
Order By: Relevance
“…This effect is mediated by reduced myogenic tone, vasoconstriction and oxidative stress. 21,22 Moreover, the vascular stiffness and fibrosis associated with ageing are prevented in mice deficient of MR in VSMCs. 23 MR activation has been shown to promote the expression of genes involved in MR-dependent vascular remodelling and calcification in VSMCs, such as collagens I and III, the integrin alpha-5 subunit, IL-16 and cytotoxic T-lymphocyte antigen-4 for vascular remodelling and genes associated with vascular calcification, such as alkaline phosphatase, parathyroid hormone receptor-2 and bone morphogenetic protein-2.…”
Section: Mr Activation In Vascular Smooth Muscle Cells (Vsmcs) Incrmentioning
confidence: 99%
“…This effect is mediated by reduced myogenic tone, vasoconstriction and oxidative stress. 21,22 Moreover, the vascular stiffness and fibrosis associated with ageing are prevented in mice deficient of MR in VSMCs. 23 MR activation has been shown to promote the expression of genes involved in MR-dependent vascular remodelling and calcification in VSMCs, such as collagens I and III, the integrin alpha-5 subunit, IL-16 and cytotoxic T-lymphocyte antigen-4 for vascular remodelling and genes associated with vascular calcification, such as alkaline phosphatase, parathyroid hormone receptor-2 and bone morphogenetic protein-2.…”
Section: Mr Activation In Vascular Smooth Muscle Cells (Vsmcs) Incrmentioning
confidence: 99%
“…2017), interaction between MR and other transcription factors such as NFkB and AP-1 (Fiebeler et al . 2001), non-genomic activation of signaling pathways that impinge on gene regulation, and suppression of miR expression by MR resulting in up-regulation of vascular miR target genes (DuPont et al . 2016).…”
Section: Mr Expression and Function In The Vasculaturementioning
confidence: 99%
“…Further studies showed that SMC-MR-KO mice generated less spontaneous vascular myogenic tone, suggesting that SMC-MR contributes to blood pressure control via alterations in vasoconstriction by changes in vascular L-type calcium channel expression and function (McCurley et al . 2012 a , DuPont et al . 2016).…”
Section: Vascular Mr In Cardiovascular Pathologiesmentioning
confidence: 99%
“…However, this phenomenon seems indeed to be an age-dependent effect, since a latter study did not validate, at protein level, the downregulation of Ca v 1.2 in aortas from young VSMC-MR-KO mice [102]. Furthermore, during the aging process, MR expression increases in resistance vessels along with a decline in the microRNA (miR)-155 abundance, suggesting that Ca v 1.2 is a downstream target of miR-155 regulation [103].…”
Section: L-type Ca 2+ Channelmentioning
confidence: 89%